Drawing ideas: a hand-drawn approach for better design - Baskinger, Mark; Bardel, William
Award-winning designers and workshop leaders Mark Baskinger and William Bardel bring us this thorough course in drawing to create better graphic layouts, diagrams, human forms, products, systems, and more. Their drawing bootcamp provides essential instruction on thinking, reasoning, and visually exploring concepts to create compelling products, communications, and services. In a unique board binding that mimics a sketchbook, Drawing Ideas provides a complete foundation in the techniques and methods for effectively communicating to clients and audiences through clear and persuasive drawings.